Determinants of spreads on sovereign bank loans: The role of credit history - Péter Benczúr; Cosmin Ilut (Magyar Nemzeti Bank, 2006)
This paper is an empirical investigation into the role of credit history in determining the spread on sovereign bank loans. It employs an error-in-variables approach used in rational-expectations-macro-econometrics to set up a structural model that links sovereign loan spreads to realized repayment behavior. Unlike the existing empirical literature, its instrumental variables method allows for distinguishing a direct influence of past repayment problems (a ”pure reputation” effect) from one that goes through increased default probabilities. Using developing country data from the period 1973-1981 and constructing continuous variables for credit history, we find that past default is a significant determinant of the spread, even after including country fixed effects. Moreover, its reduced-form effect is very similar to its structural form effect, indicating that most of the influence of past repayment problems is through the reputation channel. Overall, past and predicted future default are substantial determinants of sovereign bank loan spreads.
Keywords: F30; F34; G12; G14; G15; 330; reputation; sovereign bank loan spreads; default risk; rational expectations; Internationaler Kredit; Länderrisiko; Rationale Erwartung; CAPM; Schätzung; Entwicklungsländer; Länderimage